Sustainable Power, Autonomous Ships, and Cleaner Energy for Future Shipping. - Hagen, John Erik (Artech House, 2021)
This exciting new book highlights and discusses new concepts for enhanced efficiency of ships and how they are operated, primarily resting on reducing the environmental footprints and operational expenses. An overview of technological and regulatory developments and drivers for the challenges described above is provided. Readers learn about sustainable energies and power for propulsion, particularly maritime electrification. The book includes shore-based initiatives on greenhouse gas reduction in shipping. Status and current practices for propulsion arrangements using renewable energy technologies are presented with examples on ships representing several categories of energies and power. Energy solutions that enable future digital and automated concepts for safe, secure, and cost-effective sustainable shipping are discussed, as well as the concept of autonomous ships as part of maritime electrification and all the possibilities.The development of renewable energies and the concept of autonomous ships provide glimpses for the development of future sustainable maritime transport solutions. Lessons learned and existing knowledge are important elements for successful transmission towards future concepts for safe, secure, and efficient maritime environmentally friendly and low-cost solutions to our sustainable power and energy challenges that lie ahead. The book discusses the work ahead and provides future thoughts on this issue.